2022
DOI: 10.1017/s0016756822000061
|View full text |Cite
|
Sign up to set email alerts
|

The petrogenesis of Early–Middle Jurassic magmatism in southern and central Mexico and its role during the break-up of Western Pangaea

Abstract: Central and southern Mexico represents a strategic place to understand the dynamics of Pangaea break-up and its influences on the evolution of the Pacific margin of North America. Lower–Middle Jurassic volcano-sedimentary successions, and scarce magmatic rocks, crop out discontinuously across this region and have been interpreted either as a vestige of a continental arc or as several deposits of syn-rift magmatism. At present, their origin is controversial. Available geochemical data on these igneous rocks sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 154 publications
(191 reference statements)
0
5
0
Order By: Relevance
“…Normalized to: P mantle (Sun and McDonough, 1989) Normalized to: Cl chondrite (Sun and McDonough, 1989) for LUP samples with a database of modern (Trans Mexican Volcanic Belt) and Mesozoic (Alisitos and NW) arcs in Mexico, as well as to the NIP Jurassic samples reported by Parolari et al (2022), it is possible to observe that LUP samples fit with the NIP ones, being equally depleted in Sr, high in Rb and with low, but variable, Nb contents (Figure 11).…”
Section: Tfs-11mentioning
confidence: 93%
See 3 more Smart Citations
“…Normalized to: P mantle (Sun and McDonough, 1989) Normalized to: Cl chondrite (Sun and McDonough, 1989) for LUP samples with a database of modern (Trans Mexican Volcanic Belt) and Mesozoic (Alisitos and NW) arcs in Mexico, as well as to the NIP Jurassic samples reported by Parolari et al (2022), it is possible to observe that LUP samples fit with the NIP ones, being equally depleted in Sr, high in Rb and with low, but variable, Nb contents (Figure 11).…”
Section: Tfs-11mentioning
confidence: 93%
“…While in northwestern Mexico the Jurassic continental magmatism is seen as the southern continuation of the Cordilleran system (see Martini and Ortega-Gutierrez, 2018, for a complete synthesis), in northeastern, central and southern Mexico Jurassic magmatism belonging to the Nazas Igneous Province (NIP) has been recently reinterpreted as crustally derived by partial melting of continental rocks during the extensional tectonics that accompanied the opening of the Gulf of Mexico, based upon a strict reinterpretation of its geochemical character (Parolari et al, 2022). The model proposed by Parolari et al (2022) also applies to isolated Jurassic rocks of southwestern Mexico, such as: (a) a Middle Jurassic pluton with an age of 165 Ma reported by Guerrero-García et al (1978) from the Acapulco -Tierra Colorada transect of the Xolapa Complex; (b) a ~158 Ma orthogneiss reported by Ducea et al (2004) from north of Puerto Escondido; and (c) the Early Jurassic Tizapa metagranite (186.5 ± 7.4 Ma, lower intercept of discordant data) in the eastern Guerrero Terrane, Teloloapan subterrane (Elías-Herrera et al 2000); (d) Jurassic, two-mica granites exposed E of the Puerto Vallarta batholith (Valencia et al, 2013;Schaaf et al, 2020). In southern Mexico a migmatization event is known in the eastern Acatlán complex (Magdalena migmatite, 175±3 and 171±1 Ma) and associated with a thermal unroofing during the breakup of Pangea (Keppie et al, 2004), thus it can be clearly ascribed to the same extensional event.…”
Section: Provenance Of the Lup Granitic Magmas: Subduction Or Rift Pr...mentioning
confidence: 99%
See 2 more Smart Citations
“…During the Mesozoic period, the continental extensional tectonics was controlled by two important geodynamic processes: the subduction of the Farallon Plate beneath the western margin of North America and the rupture of Pangaea during Late Triassic-Middle Jurassic time (e.g. Martini & Ortega-Gutiérrez, 2018;Parolari et al 2022). Martini suggested that the Late Jurassic to Early Cretaceous back-arc spreading of the Arperos Basin separated the Guerrero terrane from the Mexican mainland.…”
Section: Geological Overviewmentioning
confidence: 99%